If it's not what You are looking for type in the equation solver your own equation and let us solve it.
g-5/5=4/5
We simplify the equation to the form, which is simple to understand
g-5/5=4/5
Simplifying:
g-1=4/5
Simplifying:
g-1=0.8
We move all terms containing g to the left and all other terms to the right.
+1g=0.8+1
We simplify left and right side of the equation.
+1g=+1.8
We divide both sides of the equation by 1 to get g.
g=1.8
| (X*0.365)+(X*.2)=100 | | 4x+5/8=5x+5/8 | | 9x-87=6x-9 | | 10-5(n+4)=11 | | -4(v+7)=7v+27 | | 6y+3(y-5)=4(y+1)-3 | | -4(4y-5)+2(2y+10)= | | Y-(1/2)=3/4 | | 0.8(0.1x+0.5)-0.8= | | 0.16(y-4)+0.08y=0.02y-0.2 | | (1+2j)=(1/12-5j) | | 32+112x-16x^2=0 | | 23=-4(n-3)+3(1+2n) | | 0.08(y-3)+0.04y=0.14-0.4 | | (7x-2)(9x+3)= | | 46x-41=7(6x-6)+4x+1 | | 0.50x+0.15(50)=33.5 | | -16*4=x | | -2y-8=6y+8 | | 2X^2-16X+16y+64=0 | | 9x+7=-5+7x+22 | | -5/8x-6=-7 | | (-87x^(1/2)/2)/x^2 | | -2(x-9)-26=-8 | | 7y+2(y-9)=3(y+1)-2 | | 5/10y-36=0 | | (x-5y)(x+5y)= | | 5y^(8/3)+7y^(5/3)-6y^(2/3)=0 | | 8/9-3/7 | | 6/12y+65=0 | | -5/7(-7) | | (3x-4)*2-(x-7)*2=8x(x-2) |